The consequences of measurement error when estimating the impact of BMI on labour market outcomes - Donal O'Neill; Olive B. Sweetman (Institute for the Study of Labor (IZA), 2012)
This paper uses data on both self-reported and true measures of individual Body Mass Index (BMI) to examine the nature of measurement error in self-reported BMI and to look at the consequences of using self-reported measures when estimating the effect of BMI on economic outcomes. In keeping with previous studies we find that self-reported BMI is subject to significant measurement error and this error is negatively correlated with the true measure of BMI. In our analysis this non-classical measurement error causes the traditional approach to overestimate the relationship between BMI and both income and education. Furthermore we show that popular alternatives estimators that have been adopted to address problems of measurement error in BMI, such as the conditional expectation approach and the instrumental variables approach, also exhibit significant biases.
Keywords: C13; C26; I14; 330; obesity; non-classical measurement error; auxiliary data; instrumental variables; Körpergewicht; Statistischer Fehler; Irland